AN INVESTIGATION INTO THE SCHOOL INFASTRUCTURE AND PREPAREDNESS IN IMPLEMETING THE PROPOSED GOVERNMENT TABLET PROJECT FOR STANDARD ONE PUPIL’S : A CASE STUDY OF KINANGOP SUB -COUNTY, NYANDARUA COUNTY, KENYA - Kahungu, Peris Gathoni; Kibaara, Tarsilla M.; Marete, Jacob Bundi (IJRDO- Journal of Educational Research, 2017)
The Government, in 2013, proposed to implement a tablet project for ICT integration in education so as to improve the quality of education in Kenya. The study therefore sought to establish the viability of this project by looking into whether teachers had the necessary ICT skills and the availability of the necessary infrastructure. The study concluded that primary schools in the Sub-County had adequate storage facilities. It was also established that all schools within are connected to mains electricity and the study concluded that the internet connectivity was poor in over half the schools. The study also noted that teachers in primary schools had ICT skills but there is need to further train teachers to enhance teaching and learning, and to raise education standards. The lack of ICT skills, time and disinterest in ICT needs to be addressed to improve the perception and attitudes of teachers towards ICT use